Comparative study of two different doses of nalbuphine attenuating hemodynamic response to laryngoscopy and intubation in patients undergoing general anesthesia - Kallapur, Basavaraj; Kiran, Bharath; Sheikh, Safiya I. (International Journal of Research in Medical Sciences, 2019)
Background: Various anaesthetic agents have been tried to attenuate pressor response to laryngoscopy and intubation. Among the recommended groups intravenous nalbuphine satisfies without much undesired effects. The objective was to study efficacy of two different doses of nalbuphine to attenuate pressor response to laryngoscopy and intubation. Methods: This was hospital based comparative study was carried out at Karnataka institute of Medical Sciences Hospital, Hubli, India. Patients were divided into two groups of 50 each randomly. First group was named as N1 and the second group was named as N2. Patients in N1 were given 0.1mg/kg Nalbuphine in 10ml of normal saline and patients in N2 were given 0.2-0.1mg/kg Nalbuphine in 10ml of normal saline. Appropriated statistical tests were applied like t test, ANOVA. P value if found less than 0.05 was recorded as statistically significant. Results: There was marked increase in HR, SBP, DBP and MAP immediately following laryngoscopy and intubation in the both the groups. Intravenous Nalbuphine given 5 minutes before intubation in the dose of 0.2mgkg-1 body weight effectively attenuated the hemodynamic response after laryngoscopy and intubation. However, there was a rise in HR, SBP, DBP and MAP immediately following intubation in group N2 which was clinically not significant though statistically significant. Side effects like nausea, vomiting, respiratory depression and sedation was not observed in both study groups. Conclusions: Authors concluded that 0.2mg/kg body weight dose of Nalbuphine was found to be more effective than 0.1mg/kg body weight dose of nalbuphine in maintaining the haemodynamics of the patients.